2017
DOI: 10.1139/cjm-2016-0511
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promotion properties of bacterial strains isolated from the rhizosphere of the Jerusalem artichoke (Helianthus tuberosusL.) adapted to saline–alkaline soils and their effect on wheat growth

Abstract: The Jerusalem artichoke (JA; Helianthus tuberosus), known to be tolerant to saline-alkaline soil conditions, has been cultivated for many years in the Yellow River delta, Shandong Province coastal zone, in China. The aim of our study was to isolate nitrogen-fixing bacteria colonizing the rhizosphere of JA and to characterize other plant growth promotion properties. The ultimate goal was to identify isolates that could be used as inoculants benefiting an economic crop, in particular for improving wheat growth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Among them, Enterobacter sp. N10 can significantly increase the root length and plant height of sunflower and wheat, and is the best rhizobia to increase wheat yield ( Liu et al., 2017 ). Also Li et al., have shown that among the 8 strains of salt-tolerant bacteria, E. cloacae HSNJ4 can promote the germination of rape seeds, balance the relative content of IAA and ethylene in seedlings, increase root length, stem length, lateral root content and chlorophyll content, and improve its salt tolerance ( Li et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Enterobacter sp. N10 can significantly increase the root length and plant height of sunflower and wheat, and is the best rhizobia to increase wheat yield ( Liu et al., 2017 ). Also Li et al., have shown that among the 8 strains of salt-tolerant bacteria, E. cloacae HSNJ4 can promote the germination of rape seeds, balance the relative content of IAA and ethylene in seedlings, increase root length, stem length, lateral root content and chlorophyll content, and improve its salt tolerance ( Li et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wheat is one of the most important cereals worldwide for human diet. Although wheat is extensively cultivated in the area of Yellow River Delta, its area of cultivation is limited due the excess of salinity and alkalinity of soils ( Liu et al., 2017 ). The “Bohai sea granary programme” that was recently launched in China has for objective to better exploit the salt-alkaline land for cereal cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose (5 g L −1 ) was used as a carbon source. Each SBR operating cycle consisted of three steps: (i) Feeding with fresh nitrogen-free culture media (Ashby) [ 22 ]; (ii) Aerobic reaction time during 24 h; and (iii) Settling of biomass during 2 h followed by supernatant removal. The two inocula (ASI and FPI) that showed the highest amount of TKN were used in the next phase (Phase 2).…”
Section: Methodsmentioning
confidence: 99%
“…Ashby Nitrogen-free medium(25): Mannitol 1 %, KH 2 PO 4 0.02 %, MgSO4·7H 2 O 0.02 %, NaCl 0.02 %, CaSO 4 ·2H 2 O 0.01 %, CaCO 3 0.5 %. Solid medium should plus agar 8 %.…”
Section: Methodsmentioning
confidence: 99%
“…In order to the isolation of bacteria, 5 g of soil sampling was transferred to sterile Ashby nitrogen-free culture medium(25) in 250 ml flasks and agitated on the temperature controlled rotary shaker to gain homogeneous suspensions (20°C, 150rpm, 24h). Then the suspended liquid (5ml) was pipetted into Ashby Nitrogen-free medium for Azotobacter accumulation and incubated under the conditions described above for secondary isolate.…”
Section: Methodsmentioning
confidence: 99%